Meningkatkan Keterampilan Make Up Fantasy Melalui Model Explicit Instruction Bagi Siswa Tuli - Wahyuni, Indah Tri; Kusumastuti, Grahita (Jurnal Penelitian Pendidikan Khusus, 2024)
This article discusses the effectiveness of the Explicit Instruction Model to improve Make Up Fantasy skills for Deaf Students. This research uses a quantitative approach to the experimental type, namely SSR (single subject research). The Single Subject Research (SSR) design form that researchers will use in this research is the A-B-A technique. Because in this research the researcher wants to see the design of the baseline phase (A1 ), intervention phase (B), and baseline phase (A2). The A-B-A design in this study consists of the initial baseline phase (A1), namely the child's initial condition before being given intervention, phase (B). Data collection techniques are in the form of observation and interview techniques and data collection tools are observation instruments. The subject of this research was a single subject, namely a student at SLB N 1 Padang Panjang with the initials PA in the deaf student category, female, 14 years old, sitting in class VII of SMPLB. The results of the study used an A-B-A design, carried out in 14 meetings divided into 3 phases, namely the baseline phase (A1) with 3 meetings getting results of 28%, 28% and 28%. The intervention phase (B) with 7 meetings getting results of 62%, 62% , 76%, 88%, 88%, 88%, and 88%. The baseline phase (A2) of 3 meetings obtained results of 90%, 95%, 95% and 95%. Based on the research results, it can be concluded that the Explicit Instruction Model can improve Make Up Fantasy skills for Deaf Students.